(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The article demonstrates the life of Marie Curie, her works in physics and chemistry, and her role in science. It also emphasizes the best creation of Marie Curie in physics with the example of radioactivity. Approaching the term “radioactivity” from the scientific point of view is highly supported in the article. This approach can help to understand how Marie Curie created radioactivity andher contribution in science